Spatial Differentiation in Urban Thermal Environment Pattern from the Perspective of the Local Climate Zoning System: A Case Study of Zhengzhou City, China - Jinghu Pan; Bo Yu; Yuntian Zhi (Atmosphere)
In order to assess the spatial and temporal characteristics of the urban thermal environment in Zhengzhou City to supplement climate adaptation design work, based on the Landsat 8–9 OLI/TIRS C2 L2 data for 12 periods from 2019–2023, combined with the lLocal climate zone (LCZ) classification of the urban subsurface classification, in this study, we used the statistical mono-window (SMW) algorithm to invert the land surface temperature (LST) and to classify the urban heat island (UHI) effect, to analyze the differences in the spatial distribution of thermal environments in urban areas and the aggregation characteristics, and to explore the influence of LCZ landscape distribution pattern on surface temperature. The results show that the proportions of built and natural landscape types in Zhengzhou’s main metropolitan area are 79.23% and 21.77%, respectively. The most common types of landscapes are wide mid-rise (LCZ 5) structures and large-ground-floor (LCZ 8) structures, which make up 21.92% and 20.04% of the study area’s total area, respectively. The main urban area’s heat island varies with the seasons, pooling in the urban area during the summer and peaking in the winter, with strong or extremely strong heat islands centered in the suburbs and a distribution of hot and cold spots aggregated with observable features. As building heights increase, the UHI of common built landscapes (LCZ 1–6) increases and then reduces in spring, summer, and autumn and then decreases in winter as building heights increase. Water bodies (LCZ G) and dense woods (LCZ A) have the lowest UHI effects among natural settings. Building size is no longer the primary element affecting LST as buildings become taller; instead, building connectivity and clustering take center stage. Seasonal variations, variations in LCZ types, and variations in the spatial distribution pattern of LCZ are responsible for the spatial differences in the thermal environment in the study area. In summer, urban areas should see an increase in vegetation cover, and in winter, building gaps must be appropriately increased.